1993
DOI: 10.1161/01.hyp.22.5.665
|View full text |Cite
|
Sign up to set email alerts
|

Arterial smooth muscle cell phenotype in stroke-prone spontaneously hypertensive rats.

Abstract: The aim of this study was to determine the phenotype of smooth muscle cells in the arteries of chronically hypertensive animals and to analyze the effects of treatments known to increase the survival of the animal without a clear effect on its hypertensive state. Stroke-prone spontaneously hypertensive rats (SHRSP) kept on a 1% sodium drinking solution were untreated or treated with one of two diuretics, indapamide (3 mg/kg per day) or hydrochlorothiazide (20 nig/kg per day), from 6 to 13 weeks of age. Phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…14,[45][46][47] Moreover, several previous studies have demonstrated the presence of less-differentiated cells in the aortas of renovascular hypertensive rabbits and stroke-prone SHRs, as suggested by the increase in nonmuscle myosin heavychain content and medial hypertrophy. 41,48,49 Our finding of an increase in EIIIA FN and its receptor in SHRs is in keeping with these data, showing that some degree of a dedifferentiation process may occur in the aortas of SHRs. The mechanical properties assessed by the in vivo E inc -stress relationship depend on both the passive MEC behavior and the phenotypic characteristics of VSMCs.…”
Section: Fn and Aortic Wall Mechanicssupporting
confidence: 89%
See 1 more Smart Citation
“…14,[45][46][47] Moreover, several previous studies have demonstrated the presence of less-differentiated cells in the aortas of renovascular hypertensive rabbits and stroke-prone SHRs, as suggested by the increase in nonmuscle myosin heavychain content and medial hypertrophy. 41,48,49 Our finding of an increase in EIIIA FN and its receptor in SHRs is in keeping with these data, showing that some degree of a dedifferentiation process may occur in the aortas of SHRs. The mechanical properties assessed by the in vivo E inc -stress relationship depend on both the passive MEC behavior and the phenotypic characteristics of VSMCs.…”
Section: Fn and Aortic Wall Mechanicssupporting
confidence: 89%
“…These results were confirmed by Western blot analysis for total FN. To our knowledge, the only published immunohistochemical study of aortic EIIIA FN in hypertension is that by Contard et al, 41 which did not show any change in EIIIA FN in stroke-prone SHRs compared with Wistar-Kyoto rats. The apparent discrepancy between that study and ours may originate from different genetic models of hypertension (SHRs versus stroke-prone SHRs), the age of the animals used, and the method used for immunohistologic staining (freeze-dried, paraffin-embedded sections versus immunofluorescence).…”
Section: Aortic Fn and ␣5␤1-integrins During Hypertensionmentioning
confidence: 77%
“…We recently found that generation of Ang II in VSMC from SHR is associated with a change from the contractile to the synthetic phenotype, and that the change to the synthetic phenotype in SHR-derived VSMC also increases the expression of the growth factors of TGF-β1, PDGF A-chain, and bFGF through increased Ang II (33). VSMC proliferation and change to the synthetic phenotype contributes to the pathogenesis of atherosclerosis (34), neointimal formation after angioplasty (35) and hypertensive vascular diseases (36) in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…79 This proliferative phenotype is closely associated with a marked upregulation in ED-A-positive FN. 79,80 Furthermore, hypertension in different rat animal models has been shown to rapidly increase ED-A-positive FN expression (3-to 6-fold), correlating with the degree of blood pressure elevation; this expression is reversed by normalization of the blood pressure.…”
Section: Fn and Hypertensionmentioning
confidence: 99%
“…79 This proliferative phenotype is closely associated with a marked upregulation in ED-A-positive FN. 79,80 Furthermore, hypertension in different rat animal models has been shown to rapidly increase ED-A-positive FN expression (3-to 6-fold), correlating with the degree of blood pressure elevation; this expression is reversed by normalization of the blood pressure. [81][82][83] Similar to FN expression in atherosclerosis, angiotensin II rapidly increases FN expression in the aortic wall after a 3-day infusion, an effect that is inhibited by angiotensin II receptor blockade and occurs independently of the increase in blood pressure.…”
Section: Fn and Hypertensionmentioning
confidence: 99%